Some aromatic compounds from dichloromethane extract of Salicornia ramosissima. - Isca, Vera M. S. (2014)
6th Spanish-Portuguese-Japanese Organic Chemistry Symposium, Lisboa, de 18 a 20 de Julho de 2012 (Poster Communication).